PENGARUH PARENTING STRESS DENGAN PERILAKU KEKERASAN TERHADAP ANAK DI KELURAHAN TANGKERANG BARAT KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Ariska, Yulia; Novianti, Ria; Kurnia, Rita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack: The study aim todetermine the effect of parenting stress with the behavior of violence in children in the village tangkerang west marpoyan damai distrct of pekanbaru city.The population of this research is in children in the village tangkerang west marpoyan damai distrct of pekanbaru city that consists of 120 parent, the samples of this research are 55 parent. Method of this research is quantitative correlation to know the correation between independent variable and dependent variable. The technique of collecting data used quistioner in Likert scale form. The technique of analyzing data used scale test and statistic analitical by using SPSS program for Windows Ver.22. Based on the hypothesis there is any significant negative correlation between parent’ parenting stress and violence behavior in children in the village tangkerang west marpoyan damai distrct of pekanbaru city. It could be seen from the result of correlation cooficient that 0,412 and significant level is 0,02 < 0,05. The correlation between students’ adversity quotient and academic procrastination is in the medium level which is the KP = r² x 100% = 17%, it means that a affect the violent behavior as much as 17%.Key Words: Parenting stress, violence behavior